Niobium Pentachloride as a Highly Efficient Catalyst for the Synthesis of Quinoxaline Derivatives - Kidwai, Mazaahir; Kumar Mishra, Neeraj; Bhatnagar, Divya; Jahan, Anwar (Asian Journal of Chemistry, 2011)
Niobium pentachloride is found to be an efficient catalyst for the synthesis of quinoxaline derivatives via the condensation of aromatic 1,2-dicarbonyl compounds (or unsymmetrical 1,2- diketones or α-hydroxy ketones) with 1,2-diamines. All the reactions were performed at room temperature while using acetonitrile as solvent. The present methodology offers several advantages such as excellent yields, short reaction time and environmentally benign milder reaction conditions.